South Meruya PPM in MSMEs Financial Management - UTAMI, Fransisca Listyaningsih; ZAMZAMI, Annisa Hakim (Indonesia Strategic Sustainability, 2024)
PPM activities target MSME partners in the Meruya Selatan Village area, West Jakarta. Based on the situation analysis, it is known that the increasing number of MSMEs in the Meruya Selatan area is facing problems related to finance, such as poor financial performance, difficulty in increasing business profits, and insignificant business development. The potential that can be developed includes the number of active MSME actors, cooperatives that accommodate MSMEs, and motivation to become entrepreneurs. Thus, the socialization of MSME management is packaged directly by determining selling prices, recording financial transactions, and providing simple financial reporting to MSME actors in the Meruya Selatan Village. This activity aims to provide knowledge and skills to MSME actors in the Meruya Selatan Village area to determine the selling price of products appropriately to avoid losses and use accounting easily to prepare simple financial reports. Understanding simple accounting helps MSME actors manage sources of funds carefully and efficiently so that MSMEs can develop better and improve the Indonesian economy.